MANAJEMEN PELATIHAN GURU DI SEKOLAH MENENGAH PERTAMA NEGERI 7 MUARO JAMBI KECAMATAN JAMBI LUAR KOTA KABUPATEN MUARO JAMBI PROVINSI JAMBI - Amelia Putri; Tuti Indriyani; Summiyani Summiyani (Jurnal Manajemen Pendidikan, 2026)
This research is motivated by the performance of teachers who have not been able to implement the training results optimally in practice, the preparation of learning which should be the basis for the implementation of teaching and learning activities has not been implemented properly by a number of teachers. This study aims to determine the Management of Teacher Training at State Junior High School 7 Muaro Jambi, Jambi Luar Kota District, Muaro Jambi Regency, Jambi Province. The approach used in this study is a descriptive approach and uses qualitative methods using data collection instruments in the form of interviews, observation and documentation. The results of this study indicate that, Teacher Training Management at State Junior High School 7 Muaro Jambi, Jambi Luar Kota District, Muaro Jambi Regency, Jambi Province has been implemented, but has not run optimally well. There are still obstacles in the implementation of training. The obstacles to teacher training include facilities and infrastructure such as the lack of a special room for training activities, time such as clashing teacher training schedules with teaching schedules, technical such as loss of network during power outages, and information technology where some teachers do not understand and are not accustomed to using laptops and digital applications. And efforts made such as Utilizing existing facilities, diverting discussion activities, preparing offline materials, rearranging training schedules. alternative learning such as students being given assignments, providing special assistance and creating IT learning modules